2021
DOI: 10.1111/apt.16326
|View full text |Cite
|
Sign up to set email alerts
|

Review article: investigation and management of internal fistulae in Crohn’s disease

Abstract: SummaryBackgroundCrohn’s disease is an inflammatory, penetrating intestinal disease associated with fistula formation. Fistulae in Crohn’s disease can be classified into external and internal fistulae. Internal fistulae form between the gastrointestinal tract and another internal organ and include enteroenteric, enterocolic, enterovesical and rectovaginal fistulae. They are associated with significant morbidity and a decreased quality of life.AimTo review the classification, diagnosis, medical and surgical man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 132 publications
0
9
0
Order By: Relevance
“…Whether these results might be obtained in penetrating disease is still to be demonstrated, and the chronic and potentially irreversible nature of these lesions could play against it (7,17). Nevertheless, no The American Journal of GASTROENTEROLOGY randomized placebo-controlled trial has directly evaluated the efficacy of biologic agents when stricturing or penetrating disease has already developed (6). In addition, surgical management should be also discussed with these patients, including aspects such as the risk of postoperative recurrence, the need for prophylactic therapy, and even further surgical interventions (18).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Whether these results might be obtained in penetrating disease is still to be demonstrated, and the chronic and potentially irreversible nature of these lesions could play against it (7,17). Nevertheless, no The American Journal of GASTROENTEROLOGY randomized placebo-controlled trial has directly evaluated the efficacy of biologic agents when stricturing or penetrating disease has already developed (6). In addition, surgical management should be also discussed with these patients, including aspects such as the risk of postoperative recurrence, the need for prophylactic therapy, and even further surgical interventions (18).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, surgical management should be also discussed with these patients, including aspects such as the risk of postoperative recurrence, the need for prophylactic therapy, and even further surgical interventions (18). Previous studies evaluating different types of fistulas and outcomes showed that anti-TNF agents may be effective in this setting (6,18), although this has been mostly in small case series and only in the short term (8,(19)(20)(21)(22)(23). In a cohort of 93 patients with penetrating disease (77% entero-enteric or entero-colonic, 17% entero-vesical, and 5% entero-vaginal), 27% of patients achieved fistula closure after 5 years of follow-up, and 47% required surgery (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations